Effects of ultrasound on zeolite A synthesis - Andaç, Özlem; Tatlıer, Melkon; Sirkecioğlu, Ahmet; Ece, Işık; Erdem-Şenatalar, Ayşe; Sirkecioğlu, Ahmet; Ungun, Ayşe Erdem (Elsevier BV, 2005)
Abstract Synthesis of zeolite A from a clear-to-the-eye sodium aluminosilicate solution was carried out in the presence of ultrasound at different temperatures and times and the results were compared to those obtained by performing conventional static syntheses under similar conditions. It was possible to obtain highly crystalline zeolite A in the presence of ultrasound, which influenced the types and stability areas of the phases that formed during metastable phase transformations. Nucleation and crystallization rates, as well as the yield of zeolite A increased as a result of the application of ultrasound. Thermogravimetric analyses and water adsorption experiments revealed that the development of micropore adsorption capacity, which started very early in the X-ray amorphous samples obtained from this so-called “clear” solution, was also speeded up with the application of ultrasound.